ANALISIS KINERJA KEUANGAN BANK UMUM SYARIAH SEBAGAI DAMPAK INEFISIENSI OPERASIONAL - Diharpi Herli Setyowati (Masoem University, 2019)
This study aims to measure and analyze the effect of operational efficiency which is proxied by bank financial ratios consisting of the ratio of Operational Costs to Operating Income (BOPO), Allowance for Earning Asset Losses (PPAP), Non-Performing Finance (NPF), to Return on Assets (ROA). The method used in this research is an explanatory method. The sample of this research is 11 Islamic Commercial Banks (BUS) with the use of purposive sampling technique in determining the sample. The data used in this study are secondary data obtained from annual bank reports from 2010 to 2018. The analysis technique used is multiple linear regression analysis. The results showed that only BOPO had a negative and significant effect on financial performance, which was proxied by ROA.